Combining Breast and Ovarian Operations Increases Complications. Issue 5 (2nd March 2022) - Henn, Dominic; Barrera, Janos A.; Sivaraj, Dharshan; Lin, John Q.; Rizk, Nada M.; Ma, Irene; Gurtner, Geoffrey C.; Lee, Gordon K.; Nazerali, Rahim S.
Abstract : Background: Breast cancer resulting from a genetic mutations, such as BRCA1 or BRCA2, is seen in 5 to 10 percent of patients. More widespread genetic testing has increased the number of affected women undergoing prophylactic mastectomy and oophorectomy. Recent studies have yielded mixed results regarding complication rates after combined breast and ovarian operations. The authors compared surgical outcomes of breast operations performed in combination with salpingo-oophorectomies or as separate procedures. Methods: The authors retrospectively analyzed surgical complications and length of hospital stay in 145 female patients, from which 87 had undergone combined breast surgery and salpingo-oophorectomy, and 58 had undergone these procedures separately. Multivariate logistic regression models were used to calculate odds ratios and 95 percent confidence intervals. Results: Patients undergoing combined breast and ovarian operations experienced higher rates of overall complications (46.5 percent versus 19 percent; p < 0.001), infections (22.2 percent versus 8.6 percent; p < 0.05), and delayed wound healing (13.2 percent versus 0 percent; p < 0.05) related to the breast surgery, when compared with patients undergoing separate procedures. Multivariate logistic regression analysis confirmed a significant association between combined surgery and overall postoperative complications (OR, 5.87; 95 percent CI, 2.03 to 16.91; p = 0.02). Patients undergoing tissue expander–based breast reconstruction combined with ovarian surgery had significantly longer hospital stays compared to patients undergoing separate procedures (3.5 days versus 1.8 days; p < 0.001). Conclusions: The authors' data indicate that combining breast and ovarian operations is associated with a higher risk of postoperative complications related to the breast procedure and increases the duration of hospital stay in patients with tissue expander–based reconstructions. The authors' study provides valuable information for preoperative counseling of patients considering both breast and ovarian surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.